POPULATION'S PERCEPTIONS ON SPATIAL DEVELOPMENT (CASE STUDY: KAYU BESAR ROAD CORRIDOR KUALANAMU INTERNATIONAL AIRPORT) - Ridwan Ridwan (Jurnal Teknologi Terapan and Sains 4.0, 2021)
Rapid economic growth in a certain area causes that area to be potentially developing in meeting people’s needs. It also influences the area of street corridor which involves various physical and non-physical aspects. The growth in street corridor can also be seen from the activities in it. Various activities in a certain area will provide its own characteristics. This condition occurs at Jalan Kayu Besar Corridor, an access to Kualanamu Airport; it has value-added compared to the other corridors. Behavior and characteristics at Tanjung Morawa and its vicinity, especially along Jalan Kayu Besar Corridor, tends to take the place of the street corridor by using it as the place for doing activities such as store buildings, offices, traditional markets, motels, gas stations, and others so that commercial area is established. The research used statistics method which was aimed to find out the correlation among the variables. The variables of the research were accessibility, urban service facility, commercial facility, environmental support capacity, and population. The result of the research showed that people’s perception on spatial space development along the corridor had significant influence on the development of the corridor in the research area.Key Words : Population’s Perception, Spatial Space, Corridor